2018
DOI: 10.1186/s40168-018-0569-2
|View full text |Cite
|
Sign up to set email alerts
|

Species-level bacterial community profiling of the healthy sinonasal microbiome using Pacific Biosciences sequencing of full-length 16S rRNA genes

Abstract: BackgroundPan-bacterial 16S rRNA microbiome surveys performed with massively parallel DNA sequencing technologies have transformed community microbiological studies. Current 16S profiling methods, however, fail to provide sufficient taxonomic resolution and accuracy to adequately perform species-level associative studies for specific conditions. This is due to the amplification and sequencing of only short 16S rRNA gene regions, typically providing for only family- or genus-level taxonomy. Moreover, sequencing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 104 publications
1
111
0
Order By: Relevance
“…The Pacific BioSciences SMRT platform has seen the greatest promise in this regard with the implementation of "Circular Consensus Sequencing" in conjunction with denoising algorithms, allowing for the production of long reads of high quality 24 . Earl et al showed that this new method using degenerate primers targeting the entire 16S rRNA gene, still resulted in off target amplification of the human genome 25 . This study also noted that this off target amplification was related to the ratio of human to bacterial DNA.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The Pacific BioSciences SMRT platform has seen the greatest promise in this regard with the implementation of "Circular Consensus Sequencing" in conjunction with denoising algorithms, allowing for the production of long reads of high quality 24 . Earl et al showed that this new method using degenerate primers targeting the entire 16S rRNA gene, still resulted in off target amplification of the human genome 25 . This study also noted that this off target amplification was related to the ratio of human to bacterial DNA.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Of comparable importance is the discrimination of bacterial communities at species level although the discrimination of fungal communities was just possible at phylum and genus levels in the present study. The use of 16S rRNA gene for the discrimination of bacterial community at species level was demonstrated in another similar study [33], while the use of ITS rRNA gene for the discrimination of fungal communities at genera level is more reliable than at species level [34]. As the present study was based on the analysis of sequenced DNA amplicons, a culture-based microbiological investigation should be conducted to determine the load of fruit peel microorganisms, thereby supplement the present analysis.…”
Section: Fungal Communitymentioning
confidence: 80%
“…We highlight that other microbiome sequencing approaches exist beyond metagenomics or 16S amplicons on a MiSeq (integrated instrument performing clonal amplification and sequencing), for example PacBio long-read sequencing ( 62 ). Earl and collaborators ( 63 ) used a CAMI dataset to test the accuracy of this method and it is therefore possible to indirectly compare Core-Kaiju with PacBio through their results. Also in this case we found that our method gives a slightly higher R 2 score for the genera abundances composition, confirming the competitiveness of Core-Kaiju even with the long-read sequencing technologies, such as PacBio.…”
Section: Discussionmentioning
confidence: 99%